The comparative analysis of BCR-ABL/ABL detection by real-time quantitative PCR and automated GeneXpert Dx System in chronic myeloid leukemia patients with major and complete molecular response - S. A. Smirnikhina; G. A. Tsaur; E. Yu. Chelysheva; Yu. A. Yakovleva; A. V. Lavrov; A. O. Аbdullaev; N. V. Bederak; O. A. Shukhov; A. G. Solodovnikov; A. M. Popov; E. P. Adilgereeva; L. G. Fechina; et al. (Онкогематология)
Key words: chronic myeloid leukemia, BCR-ABL expression, automated GeneXpert method